Сакральність у мовотворчості М. Рильського - Коць, Т. (Культура слова, 2020)
Стаття присвячена аналізові мовних засобів сакральності як
стильової категорії, що охоплює урочисто-піднесений, традиційно
усталений регістр експресивних мовних засобів на позначення
ціннісних домінант образних книжних синтагм релігійного стилю.
Особливу увагу звернено на розкриття стилістичного потенціалу
біблійних слів і висловів у ранній мовотворчості М. Рильського.
Розкрито мовні механізми сакральності як засобу створення
мовного колориту, урочистої, піднесеної тональності, естетичної
довершеності, позитивнооцінного звучання поетичного слова.
Виконуючи стилістичну, композиційну, прагматичну функції у
художньому тексті, сакральні одиниці є виразниками індивідуально-
авторської рецепції мови Святого письма і водночас виявом тяглості
духовної пам’яті нації. The article is devoted to the analysis of linguistic means of sacrality as
a style category, covering the solemnly elevated, traditionally established
register of expressive linguistic means that hold the dominant values of the
figurative book syntagms of religious style. Particular attention is paid to
the unveiling of the stylistic potential of biblical words and expressions in
the early speech-making of Maksym Rylskyi. The linguistic mechanisms
of sacrality as a means of creating linguistic color, solemn, sublime,
aesthetic perfection, positively-valued sounding of a poetic word are
revealed. Performing stylistic, compositional, pragmatic functions in the
artistic text, the sacral units are expressions of the individual-authorial
reception of the values.
Traditional artistic means of expressing sacrality in Maksym Rylskyi’s
language are biblical words and phraseologisms, which are included in the
registers not only of dictionaries of biblical words and expressions, but
also of common phraseological and interpretative dictionaries dominant in
the figurative book syntagms of the religious style and at the same time the
expression of the gravity of the spiritual memory of the nation. In poetic
contexts biblical words and expressions often acquire a metaphorical,
lyrical sound, attesting to the sacral desemantization of lexemes, but
instead actualizing implicit linguistic semantics.